2017
DOI: 10.1101/150052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian Comparison of Explicit and Implicit Causal Inference Strategies in Multisensory Heading Perception

Abstract: The precision of multisensory heading perception improves when visual and vestibular cues arising from the same cause, namely motion of the observer through a stationary environment, are integrated. Thus, in order to determine how the cues should be processed, the brain must infer the causal relationship underlying the multisensory cues.In heading perception, however, it is unclear whether observers follow the Bayesian strategy, a simpler non-Bayesian heuristic, or even perform causal inference at all. We deve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 78 publications
2
62
1
Order By: Relevance
“…In such tasks, the 293 observer receives sensory measurements of possibly discrepant cues from distinct sensory 294 modalities (e.g., vision and hearing), and has to infer whether the cues originated from 295 the same source (C = 1) or from different sources (C = 0) -leading to, respectively, cue 296 integration and cue segregation. Previous work has shown that Bayesian causal inference 297 models provide a good qualitative description of human performance in multisensory 298 perception with discrepant cues, but quantitative comparison hints at deviations from 299 exact Bayesian behavior [30], not unlike what we find here. Our study differs from 300 previous work in that here we focus on an atomic form of perceptual organization.…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…In such tasks, the 293 observer receives sensory measurements of possibly discrepant cues from distinct sensory 294 modalities (e.g., vision and hearing), and has to infer whether the cues originated from 295 the same source (C = 1) or from different sources (C = 0) -leading to, respectively, cue 296 integration and cue segregation. Previous work has shown that Bayesian causal inference 297 models provide a good qualitative description of human performance in multisensory 298 perception with discrepant cues, but quantitative comparison hints at deviations from 299 exact Bayesian behavior [30], not unlike what we find here. Our study differs from 300 previous work in that here we focus on an atomic form of perceptual organization.…”
contrasting
confidence: 55%
“…25 A fully Bayesian approach to perceptual organization would provide a normative 26 way for dealing both with high-level uncertainty arising from ambiguity in the latent 27 structure of the scene, and with low-level (sensory) uncertainty arising from noise in 28 measuring primitive elements of the scene. Crucially, however, previous studies in 29 perceptual organization have not examined whether the decision rule adapts flexibly as 30 function of sensory uncertainty. Such adaptation is a form of probabilistic computation 31 and is one of the basic signatures of Bayesian optimality [7].…”
Section: Author Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 532 we use a simplified, "custom" likelihood function for model fitting (Appendix B). We use the 533 Bayesian Adaptive Direct Search (BADS) method (Acerbi & Ma, 2017) to find the parameters 534 that maximise this function. In order to reduce the risk of terminating in local maxima, we run 535 BADS thirty times with different initial parameter values.…”
Section: Model Fitting Methods 530mentioning
confidence: 99%